Transcription Mapping of Embryonic Rat Brain Reveals EGR-1 Induction in SOX2+ Neural Progenitor Cells - Wells, Timothy; Rough, Kirsty; Carter, David A. (Frontiers in Molecular Neuroscience, 2011)
Neuronal expression of the EGR-1 (NGFI-A/Zif268) transcription factor has been extensively studied in the adult mammalian brain and linked to aspects of mature physiological/behavioural function. In contrast, this factor has not been studied in detail in the embryonic brain. Here, we used a fluorescent protein-encoding Egr-1 transgene to map the cellular distribution of Egr-1 transcription in embryonic rat brain. We identified a novel, widely-distributed population of GFP+ cells, characterized as a precursor/stem cell phenotype by co-localization with SOX2/nestin/vimentin/S-100β and exclusion from other known cellular markers including DCX/BLBP/TBR2/NURR1. At both E18 and E20, these cells were located across the developing brain but concentrated in the subplate and intermediate zones. The transgene was also highly expressed in developing (NeuN+) striatal neurons. The authentic expression pattern that we observed for the rEgr-1 transgene sequence indicates that restriction to neuronal/precursor cells is largely driven by proximal 5’ sequence. Deletion of conserved Egr-1 silencer (NRSF) elements did not markedly alter transcriptional activity in transfected cells; this is consistent with a dominant role for positive factors in the control of cell-specific Egr-1 expression. Induction of Egr-1 in a population of Sox2+ cells indicates a co-incidence of extrinsic (EGR-1) and cell-intrinsic (SOX2) cellular signals that may form a novel level of progenitor cell regulation. The wide distribution of EGR-1 signaling in SOX2+ cells suggests an organizational role during late embryonic brain development.